2017
DOI: 10.15171/jcs.2017.022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Belongingness Sense of Undergraduate Nursing Students towards Clinical Setting: A Qualitative Study

Abstract: Introduction: One of the most important needs of the students to work reliably in the clinical setting is the feeling of belongingness. Understanding and recognizing such a distinguishing feature among students can reduce their stress and tension. The current research aimed at studying the experiences of belongingness among nursing students in clinical settings. Methods: In this conventional content analysis study, 12 nursing students were selected from Lorestan University of Medical Sciences by purposive met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 28 publications
2
18
1
2
Order By: Relevance
“…An investigation of the stress level in clinical practice according to general characteristics showed that having family that can act as a support group appeared to decrease stress in clinical practice, which was also the case for participants in better health, who had chosen the major due to their personal suitability, and who had higher levels of satisfaction with their major, all of which is consistent with Kim and Lee 26 and Ashktorab et al 39 This also seems to support a previous study, 40 where people fitting these criteria had greater confidence in their work and were more proactive in social activities. Therefore, it is important to assist in managing student health through university health programs.…”
Section: Discussionsupporting
confidence: 73%
“…An investigation of the stress level in clinical practice according to general characteristics showed that having family that can act as a support group appeared to decrease stress in clinical practice, which was also the case for participants in better health, who had chosen the major due to their personal suitability, and who had higher levels of satisfaction with their major, all of which is consistent with Kim and Lee 26 and Ashktorab et al 39 This also seems to support a previous study, 40 where people fitting these criteria had greater confidence in their work and were more proactive in social activities. Therefore, it is important to assist in managing student health through university health programs.…”
Section: Discussionsupporting
confidence: 73%
“…In a systematic review (26), it was determined that simulation had positive effects on improving senses of confidence and effectiveness in similarity to our study. In a study that was conducted in Iran, it was found that a safe and supportive clinic environment brought more occupational sense of belonging in midwifery students, in contrast to our findings (27). These different findings could have emerged due to advantages and disadvantages of the clinic, besides different cultures.…”
Section: Discussioncontrasting
confidence: 99%
“…The studies conducted on nursing students’ perception of clinical setting indicate that nurses should welcome students and treat them with respect. 25,29 Based on the experiences of the participants in Ashktorab et al’s 30 study, feeling of worthiness affects students’ feeling of belongingness and professional ethics. Also, in the study of Borhani et al, some students considered behavior of some nursing staff discouraging in terms of ethical work and stated that they were part of their lack of power in clinical settings due to lack of support from their colleagues.…”
Section: Discussionmentioning
confidence: 99%